2017
DOI: 10.1111/vox.12596
|View full text |Cite|
|
Sign up to set email alerts
|

High platelet content can increase storage lesion rates following Intercept pathogen inactivation primarily in platelet concentrates prepared by apheresis

Abstract: Background Pathogen inactivation methods for platelet concentrates are increasingly being used in blood banks worldwide. In vitro studies have demonstrated its effects on storage lesion, but little routine quality control data on blood banking outcomes have been reported. Materials and MethodsSwirling of distributed products was monitored before and after implementation of Intercept pathogen inactivation. Metabolic parameters pH, glucose and lactic acid were determined in a random cohort of expired pathogen-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 23 publications
(19 reference statements)
1
16
1
Order By: Relevance
“…Similar findings were reported in human PC, with the report of significant differences in glucose, lactate, pH, pCO 2 , bicarbonate and ATP values in PC with high platelet counts on day 5 of storage [15]. Another study also reported a faster decrease of swirling, pH and glucose values in PC with high platelet counts when compared with those with lower platelet counts [16]. Our data on PDW and MPV indicate that platelets in the PC with lower than average counts may present less swelling and lower fragmentation rates.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Similar findings were reported in human PC, with the report of significant differences in glucose, lactate, pH, pCO 2 , bicarbonate and ATP values in PC with high platelet counts on day 5 of storage [15]. Another study also reported a faster decrease of swirling, pH and glucose values in PC with high platelet counts when compared with those with lower platelet counts [16]. Our data on PDW and MPV indicate that platelets in the PC with lower than average counts may present less swelling and lower fragmentation rates.…”
Section: Discussionsupporting
confidence: 86%
“…Our data on PDW and MPV indicate that platelets in the PC with lower than average counts may present less swelling and lower fragmentation rates. When PC contains a high number of platelets per volume, oxygen is consumed faster, and the metabolic pathway used by platelets becomes anaerobic with consequent lactate production and decrease in pH [15,16]. Still, a higher plasma volume per bag increases the transfusion volume and the risk of transfusion reactions [7,9].…”
Section: Discussionmentioning
confidence: 99%
“…Platelets produced by the TER pooling sets did have an increased lactic acid production rate. This may follow the platelet concentration and/or content because we previously showed that PI treatment can increase storage lesion when the platelet number is high [2,12]. Whether this underlies the difference in lactic acid found in this study is not clear.…”
Section: Discussionmentioning
confidence: 79%
“…Platelet yield and platelet quality were determined at different time-points during and after PC preparation. The primary criteria for PC prepared by each of these pooling sets were (1) effective leucocyte depletion (<10 6 leucocytes per unit), (2) compatibility with the available equipment including separators, centrifuges and PI sets and (3) fulfil all criteria for transfusable PI-treated platelets as set by the Blood Service.…”
Section: Introductionmentioning
confidence: 99%
“…There are two additional systems commonly studied: Mirasol (TerumoBCT, USA), approved for use in other countries, which combines riboflavin and broad-spectrum UV light (265-370 nm); and Theraflex UV Platelets (Macopharma, France), currently under development using 254 nm UV-C light (10,11). However, available PRTs do affect product quality in vitro and function in vivo, following transfusion (12)(13)(14). The ideal PRT would be relatively inexpensive, simple to implement and, with no or minimal effect on the quality or efficacy of the transfusion product (15).…”
Section: Introductionmentioning
confidence: 99%